Therapeutic Potential of Ginsenosides as an Adjuvant Treatment for Diabetes - Bai, Litao; Gao, Jialiang; Wei, Fan; Zhao, Jing; Wang, Danwei; Wei, Junping (Frontiers in Pharmacology, 2018)
Ginseng, one of the oldest traditional Chinese medicinal herbs, has been used widely in China and Asia for thousands of years. Ginsenosides extracted from ginseng, which is derived from the roots and rhizomes of Panax ginseng C. A. Meyer, have been used in China as an adjuvant in the treatment of diabetes mellitus. Owing to the technical complexity of ginsenoside production, the total ginsenosides are generally extracted. Accumulating evidence has shown that ginsenosides exert antidiabetic effects. In vivo and in vitro tests revealed the potential of ginsenoside Rg1, Rg3, Rg5, Rb1, Rb2, Rb3, compound K, Rk1, Re, ginseng total saponins, malonyl ginsenosides, Rd, Rh2, F2, protopanaxadiol (PPD) and protopanaxatriol (PPT)-type saponins to treat diabetes and its complications, including type 1 diabetes mellitus, type 2 diabetes mellitus, diabetic nephropathy, diabetic cognitive dysfunction, type 2 diabetes mellitus with fatty liver disease, diabetic cerebral infarction, diabetic cardiomyopathy, and diabetic erectile dysfunction. Many effects are attributed to ginsenosides, including gluconeogenesis reduction, improvement of insulin resistance, glucose transport, insulinotropic action, islet cell protection, hepatoprotective activity, anti-inflammatory effect, myocardial protection, lipid regulation, improved glucose tolerance, antioxidation, improvement of erectile dysfunction, regulation of gut flora metabolism, neuroprotection, anti-angiopathy, anti-neurotoxic effects, immunosuppression, and renoprotection effect. The molecular targets of these effects mainly contains GLUTs, SGLT1, GLP-1, FoxO1, TNF-α, IL-6, caspase-3, bcl-2, MDA, SOD, STAT5-PPAR gamma pathway, PI3K/Akt pathway, AMPK-JNK pathway, NF-κB pathway and endoplasmic reticulum stress. Rg1, Rg3, Rb1, and compound K demonstrated the most promising therapeutic prospects as potential adjuvant medicines for the treatment of diabetes. This paper highlights the underlying pharmacological mechanisms of the anti-diabetic effects of ginsenosides.